Experimental Study on Stress Corrosion of 20 Carbon Steel in Liquid Ammonia - YANG Quanyi (Cailiao Baohu)
An in-depth investigation into the stress corrosion behavior of 20 carbon steel in liquid ammonia and its influencing factors is of great significance.In this study，immersion tests and slow strain rate tension (SSRT) experiments were carried out to examine the corrosion and stress corrosion behavior of 20 carbon steel in liquid ammonia，and to evaluate its corrosion rate and stress corrosion susceptibility.Results showed that，in liquid ammonia，when the experimental pressure increased from 1 MPa to 2 MPa and then to 4 MPa，the corrosion rate of 20 carbon steel increased slightly，and its stress corrosion susceptibility increased.The stress corrosion susceptibility index of 20 carbon steel in liquid ammonia remained consistently above 35%，indicating it was in a highly stress corrosion sensitive region.